The Laboratory Diagnosis of Sexually Transmitted Infections in Cases of Sexual Assault and Abuse - Max A Chernesky; Colin Hewitt (Canadian Journal of Infectious Diseases and Medical Microbiology)
Laboratory staff dealing with samples from victims must be aware that such patients have been psychologically traumatized and deserve special care. The help of a sexual assault care team should be sought if available, and appropriate specimens should be collected two to 10 days after an incident, preferably in a single visit. Specimens should be clearly labelled, and the laboratory should be informed. In the laboratory, all procedures need to be clearly documented. There are special requirements for the collection of forensic specimens and associated records, which may later be required for legal proceedings. The laboratory must know what the current legal status is for any test being used in that community. The present article serves as a guideline to more detailed practice standards for the investigation of individual sexually transmitted infections in assault and abuse situations.